Rancang Bangun Sistem Informasi Pencatatan Pembayaran Berbasis Payments Writer Application terhadap Transparansi Data Keuangan Sekolah di RA H. Achmad Ali Surabaya - Aris Imawan; Ahmad Syatori; Fitria Fitria (Journal on Education, 2023)
Financial problems are part of the problems in educational organizations that must be mitigated properly and correctly. RA is no exception. H. Achmad Ali Sememi Benowo who incidentally was part of an educational organization with all kinds of problems he faced, especially in financial management. Therefore, it is necessary to have financial management in education using the principle of transparency. The purpose of this research is to find out the design of payment recording information system based on payments writer application on the transparency of RA's financial data. H. Achmad Ali Sememi Benowo Surabaya. This research uses a qualitative approach with a descriptive type. Data collection techniques use observation, interviews and documentation which are then analyzed by reducing data, displaying data, and verifying data. Lack of RA knowledge. H. Achmad Ali Sememi Benowo Surabaya will have a digital-based information system that makes recording of payments done manually which has the potential for errors in payments. So it is necessary to record payments based on the payments writer application in RA. H. Achmad Ali Sememi Benowo Surabaya with the following stages: planning, analysis, design, implementation and use and system audit. So that all kinds of errors in school financial records can be minimized